Alarmins as biomarkers of gastrointestinal surgical injury – a pilot study. Issue 2 (25th January 2018) - Maca, Jan; Holub, Michal; Bursa, Filip; Ihnat, Peter; Reimer, Petr; Svagera, Zdenek; Burda, Michal; Sevcik, Pavel
Abstract : The dysregulation of inflammatory response to surgical injury affects outcomes. Alarmins, the earliest bioactive substances from damaged cells, play a crucial role in initiating the inflammation. We analyzed serum levels of alarmins (S100A8, S100A12, high mobility group box, and heat shock protein 70) after major abdominal surgery (MAS) in surgical (S) (n = 82) and nonsurgical (NS) groups (n = 35). The main objective was determining a role of selected alarmins in host response to MAS. The secondary objectives were (i) evaluation of the relationship among alarmins and selected biomarkers (C‐reactive protein, interleukin‐6), (ii) influence of the place of gastrointestinal resection, and (iii) role of alarmins in MAS for cancer. Except for HMGB1, the levels of all alarmins were higher in the S group compared with the NS group. In the S group, positive correlations were found between S100A8 and both IL‐6 and CRP. Additionally, the S100A8 level was higher (p < 0.01) in patients who underwent upper gastrointestinal tract (GIT) surgery compared to middle and lower GIT resections. Alarmins levels did not differ between cancer and noncancer patients. MAS is able to elicit increase in alarmin levels. S100A8 can be considered a potential biomarker of surgical injury, especially in the upper part of the GIT.